The Application of Case Based Leaning Combine with Simulation of Point-Of-Care Ultrasonography in Under-Graduate Medical Students - Xin, Zheng; Chengming, You; Yangjun, Zhang; Linyan, Zhao (British Journal of Healthcare and Medical Research, 2022)
Point of care ultrasound (POCUS) has the advantage of timely,dynamic and radiation-free, POCUS has an excellent diagnostic and treatment accuracy many critical ill such as acute heart failure ,pneumothorax, pulmonary edema, is most important diagnostic tool and can used as the initial clinical assessment for critical and emergency department. Simulation of point-of-care ultrasonography based education play a more important role in the education of medical students, combined with case-based learning can be used for anesthesia under-graduate students training to improve clinical skill rapidly. After standardized training, undergraduates can quickly use POCUS for evaluation of critical patients and improve core clinical competence .